Enhancement and Maintenance of Infant Incubators at Sukodono Health Centre in Sidoarjo: Efforts to Ensure Continuity of Healthcare Services - Kholiq, Abd.; Syaifudin; Lamidi (Frontiers in Community Service and Empowerment, 2024)
Health Development is a prominent program among 45 essential initiatives that must be implemented nationwide in relation to sectoral and regional development, ranking 12th among them. In Surabaya, health programs are conducted through community health centers (puskesmas). One of the services provided at the Sukodono Health Center (PKM) includes interchangeable rooms. The Sukodono Sidoarjo Health Center also features a delivery room and infant incubator equipment designed for premature infants. The use of infant incubators significantly increases the percentage of safely born babies and enhances their ability to survive hypothermia. However, the growing sophistication of medical devices raises concerns about their safety and the reliability of infant incubators, emphasizing the need for controlled parameter inspections in medical devices. Safety inspections and performance evaluations are carried out by clinical professionals. Unfortunately, maintenance activities at the community health center have not yet been addressed due to the absence of staff qualified to handle such tasks. As part of community service, maintenance activities for infant incubator equipment were conducted to ensure that the incubators are ready and suitable for use, enabling ongoing services. The results of these activities indicated that the infant incubators are in good condition and ready for use. The measurement results show that the biggest error occurred at the baby incubator temperature which was set at 35°C with an error of 0.05°C..